Evaluation of Service Quality: Aviation Security, Customer Value and Airport Accessibility (Library Research) - Gratia Atanka Barus; Kamsariaty; Prima Widiyanto; Dewi Ulfah Arini; Mochammad Subagio (Greenation International Journal of Tourism and Management, 2024)
Abstract: Within the field of marketing management science, the paper assessing service quality: aviation security, customer value, and airport accessibility is a scientific literature review. The goal of this essay is to develop a hypothesis about the relationship between factors so that it can be utilized for future studies in the field of human resource management. The descriptive qualitative research methodology is applied. Relevant data from earlier studies was gathered for this study from academic web resources like Publish or Perish, Google Scholar, digital reference books, and Sinta journals. The findings of this paper are as follows: 1) Aviation security influences the evaluation of service quality; 2) Customer value influences the evaluation of service quality; and 3) Airport accessibility influences the evaluation of service quality. Keyword: Evaluation of Service Quality, Aviation Security, Customer Value, Airport Accessibility